2022
DOI: 10.1149/1945-7111/ac7083
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formed Edge-Rich Ni3S2-NiOOH Heterojunctions for Oxygen Evolution Reaction

Abstract: Developing highly active, earth-abundant, and durable electrocatalysts is desired but challenging for oxygen evolution reaction (OER). In this work, we design an electrocatalyst of the edge-rich nickel sulfide arrays on the nickel foam (Ni3S2 NSs-NF) by a facile yet efficient wet-chemical method. Benefiting from the three-dimensional nanostructure with numerous active edges, the prepared Ni3S2 NSs-NF exhibits superior OER performance in alkaline conditions. An in-depth study reveals that the real active sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…[56,57] Moreover, due to the in situ gen-erated Ni 3 S 2 /NiOOH heterostructure, the Ni/TiO 2 @Ni 3 S 2 electrode exhibited excellent electrocatalytic stability and exposed numerous active sites for OER and GOR reactions. [58][59][60] The SEM and TEM results showed that the morphology of Ni/TiO 2 @Ni 3 S 2 changed more seriously after the GOR reaction. As displayed in Figure 5E a large number of irregular nanosheet thick layers covered on the electrodes after GOR reaction, and HRTEM (Figure 5F) revealed the presence of NiOOH.…”
Section: Resultsmentioning
confidence: 99%
“…[56,57] Moreover, due to the in situ gen-erated Ni 3 S 2 /NiOOH heterostructure, the Ni/TiO 2 @Ni 3 S 2 electrode exhibited excellent electrocatalytic stability and exposed numerous active sites for OER and GOR reactions. [58][59][60] The SEM and TEM results showed that the morphology of Ni/TiO 2 @Ni 3 S 2 changed more seriously after the GOR reaction. As displayed in Figure 5E a large number of irregular nanosheet thick layers covered on the electrodes after GOR reaction, and HRTEM (Figure 5F) revealed the presence of NiOOH.…”
Section: Resultsmentioning
confidence: 99%
“…Fossil fuels are running out and the planet is getting worse, meaning it is really important to develop high-power and energy density alternative energy devices. There is no doubt that hydrogen (H 2 ) is a renewable and clean energy that can be obtained from the environment [ 1 , 2 , 3 , 4 ]. It is well known that hydrogen is the most abundant element on earth; currently, 90% of H 2 is acquired from fossil fuels, leading to the aggravation of the energy crisis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, vast promising transition-metal-based catalysts were designed based on phase engineering, , defect engineering, , and multimetal engineering , to increase the intrinsic activity and the number of exposed active sites or tune the intrinsic electric properties via atomic/molecular orbital coupling. , Among them, transition-metal phosphides have shown excellent catalytic activity in electrolytic water due to the multiple electron orbitals of phosphorus and the good binding energy to hydrogen (H) in different reaction media . However, most of these materials show reduced electroactive sites and reduced conductivity due to the formation of segregated multiphase clusters during the synthesis process, thus weakening the electrochemical activity .…”
Section: Introductionmentioning
confidence: 99%